Severity scale of cervicofacial cellulitis with a clinical experience - Jacques Gérard Edouma Bohimbo; Karl Guy Grégoire Kwedi; Stive Tamoh Fokam; Françis Daniel Nkolo Tolo; Marius Félix Mboya; Charles Bengondo Messanga (Elsevier, 2023)
Introduction: Severe cervicofacial cellulitis are emergencies, mostly of odontogenic origin, and frequently observed in developing countries. Their management is still a challenge despite the improvement of the antibiotic therapy these last decades. We highlight our experience in the management of this life-threatening condition. Material and methods: This was a descriptive and prospective study of all patients presenting with severe cervicofacial cellulitis between December 2020 and February 2021 in the odontostomatology department of the Garoua Regional Hospital (Cameroon). The data concerning demography (age, sex), clinical manifestations, treatment, and prognosis were analysed using SPSS version 20.0. Results: 45 cases of severe cervicofacial cellulitis were diagnosed, representing 13.76% of the total consultations. The female represented 55.55%. The mean age was 32.6 years. The main aetiology was odontogenic (93.33%). Clinical manifestations included swelling (100%), pain (100%), trismus (88.89%), dysphagia (53.33%), asthenia (35.56%), sepsis (4.44%). The main location involved was submandibular (75.56%). The overall severity score revealed the extremely high (24.44%), high (33.33%), and moderate (42.22%) grades. The antibiotic therapy was systematically administered. Short-course corticosteroids (46.67%), surgical debridement (88.89%), and etiological treatment (68.89%) were associated. Complications occurred in 13.33% of cases. The evolution was favourable in 95.56% of cases. Conclusion: The severity of cervicofacial cellulitis can be assess with a proper recognition and evaluation of the clinical signs. This will allow the practician to better manage these conditions and to improves their prognosis.